2011
DOI: 10.5402/2011/245417
|View full text |Cite
|
Sign up to set email alerts
|

Leading Change and Advancing Health by Enhancing Nurses' and Midwives' Knowledge, Ability and Confidence to Conduct Research through a Clinical Scholar Program in Western Australia

Abstract: This paper reports on an evaluation of a Clinical Scholar Program initiated at a hospital in Western Australia. The aim of the program was to build the capacity of nurses and midwives to conduct research and evidence-based practice within the hospital. The program was based on a previous program and consisted of six teaching days and four hours per month release for proposal preparation. At the end of the program participants were asked to complete a short anonymous questionnaire. The answers were analysed usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…From 7,544 initial citations, 4,974 unique abstracts were screened after duplicates were removed, 483 full-text articles were reviewed, and 81 studies 37–117 were included in the final analysis (Figure 1). Of the 81 included studies, 65 (80.2%) were published from 2011 to 2020, with 23 (28.4%) published in 2019 and 2020.…”
Section: Resultsmentioning
confidence: 99%
“…From 7,544 initial citations, 4,974 unique abstracts were screened after duplicates were removed, 483 full-text articles were reviewed, and 81 studies 37–117 were included in the final analysis (Figure 1). Of the 81 included studies, 65 (80.2%) were published from 2011 to 2020, with 23 (28.4%) published in 2019 and 2020.…”
Section: Resultsmentioning
confidence: 99%
“…A midwife/nurse mentor program in Australiawas initiated to address research-related gaps, and showed an improvement in midwives’ basic knowledge and awareness of the value of midwifery research, in addition to having the confidence to lead research. 31 Such initiatives have to be financed and sustained well to enable midwives with research-related compskillsetencies. This was evidenced in this study, where good research knowledge was noted among midwives who had taken research courses and participated in research, and a study in Turkey.…”
Section: Discussionmentioning
confidence: 99%
“…Diverse approaches to development and implementation of nursing RCB models include those that involve linkages to universities with a formal training program and a funded academic consultancy (Chapman, Duggan, & Combs, 2011;English, 2016;Larson, Cohen, Gebbie, Clock, & Saiman, 2011). Other models operate within formal funding packages (McKee et al, 2017;Trytten, Wale, Hayes, & Holmes, 2019).…”
Section: Discussionmentioning
confidence: 99%